2011
DOI: 10.1177/1352458511426736
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between walking, manual dexterity, cognition and activity/participation in persons with multiple sclerosis

Abstract: The proposed cut-off values in the 2 × 5 m walk test and the Nine-hole Peg Test may be used as indicators of functioning and to identify persons risking activity limitations and participation restrictions. However, further studies are needed to confirm the usefulness in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
93
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(96 citation statements)
references
References 26 publications
3
93
0
Order By: Relevance
“…Indeed, increased social participation was perceived by a widevariety of persons with MS, and identified in high-quality studies. Social participation is negatively correlated with a range of clinical MS outcomes [74,75] in persons with MS, leading to decreased health and economic burdens [75]. Therefore, it is important that the most common perceived social outcome was increased social participation and this finding should fuel further study into the participatory benefits of physical activity and exercise.…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, increased social participation was perceived by a widevariety of persons with MS, and identified in high-quality studies. Social participation is negatively correlated with a range of clinical MS outcomes [74,75] in persons with MS, leading to decreased health and economic burdens [75]. Therefore, it is important that the most common perceived social outcome was increased social participation and this finding should fuel further study into the participatory benefits of physical activity and exercise.…”
Section: Discussionmentioning
confidence: 98%
“…1 Versus activity/participation measures ( Table 3). The 10MTW walking speed was moderately to strongly correlated with measures of independence in ADL and participation in social and lifestyle activities, 37 and the 6mWT distance was strongly correlated with the Barthel index score, a measure of functional independence in ADL. 22 Slower walking time on the 10MTW and shorter distances walked on the 6mWT were among the most significant predictors of perceived difficulties in performing ADL in MS patients.…”
Section: Fssmentioning
confidence: 97%
“…39,50 Another study found a 1 m/sec change in the 10MTW had good sensitivity and specificity for predicting limitations in activities and participation in ADLs. 37 The smallest reliable change in the 30MTW at forced walking speed was an increase of 40% or a decrease of 29% in time based on day-to-day variability. 13 Walking distance assessments.…”
Section: Responsivenessmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, studies in older adults and in people with disease states such as stroke have shown that grip strength is predictive of poorer health status, worse outcomes including loss of independence, and increased morbidity and mortality. [9][10][11] In people with MS, manual dexterity, assessed using the 9-Hole Peg Test, was shown to be a useful indicator of risk for activity limitations and participation restrictions such as ability to perform activities of daily living (ADLs), 12 Additionally, the magnitude of UE impairment was shown to affect the level of independence and to negatively impact quality of life. 13 Subtle UE dysfunction may be present even in early MS, affecting performance of manipulation tasks and having a functional impact by producing disability and reducing the ability to perform ADLs.…”
Section: Upper Extremity Function In Msmentioning
confidence: 99%